Review of Important Brand Loyalty Influencing Factors: State of Art - Shaban, Omar Kassim A.; Liu, Yao; Mohd Ridzuan, Nordin; Alkhateeb, Abdullah N. A. (Medwell Journals, 2017)
Brand loyalty is no longer a new concept but the importance of brand loyalty could never be overstated especially in recent decades as market competitions become globally fierce. Hence, to correctly underderstand the behavior of their customers or rather the antecedents of brand loyalty could be beneficial to marketers or entrepreneurs to secure their market positions. Thus, an increasing nwnber of scholars have devoted to exploring the influencing factors of brand loyalty from various theoretical and industrial backgrormds. This study reviews the related academic studies on brand loyalty and particularly analyzes the influencing factors of Brand loyalty. It starts with introducing the evolution of brand loyalty research then defines brand and brand loyalty. Fwi:her, after revisiting the grollllded theories of brand loyalty research such as the Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM) a summary of the most frequently researched influencing factors is presented. It is hoped that the study could shed some light in facilitating researchers to further develop conceptual framework and conduct empirical research and also guiding practitioners in rationalizing market strategy.